Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Keterampilan Proses Sains Model Bounded Inquiry Laboratory Pada Materi Bioteknologi - Naibaho, Amanda Nurul Aisyah; Khairuna, Khairuna (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop and produce a product in the form of a valid and practical science process skill-based LKPD that can improve students’ skills in science process skills. The research methodology used is research and development (R&D) using the 4D development model. Data collection was carried out through interviews, questionnaires, and tests. The data analysis method used is qualitative descriptive analysis. The results of this study indicate that the developed LKPD is feasible to use. Based on the results of observations and interviews, LKPD is able to facilitate students to conduct investigations and play an active role in the learning process so that it can improve the results of students’ scientific work. The percentage of effectiveness achieved was 88.625% (very effective) and the level of practicality was 92.5% (very practical). The results of the N-Gain test showed an average N-Gain of 0.5709 (moderate) and a percentage of 57.09% (quite effective). Thus, it can be concluded that the developed LKS is feasible to use in learning activities and can improve students’ science process skills.